Appraisal and Prospects of the Second Five Year Plan May, 1958 - Planning Commission (Planning Commission, 1958)
This Memorandum on the Appraisal and Prospects of the Second Five Year Plan was submitted by the Planning Commission to the National Development Council which met on the 3rd and 4th May, 1958. The Council considered the question of the total outlay to be undertaken in the public sector during the period of the Plan in the light of the progress made during the past two years and the steps taken to raise additional resources. It was decided that the total outlay should be maintained at Rs. 4,800 crores. In view, however, of the assessment of resources made by the Planning Commission, the Council considered that the projects and programmes to be undertaken within the ceiling of Rs. 4,800 crores.
Government of India Planning Commission